Efficacy of small incision cataract surgery in community based eye camps: a report from Sindupalchowk, Nepal - Gautam, P; Dhungel, P; Adhikari , HB; Dhungel , S (Journal of Institute of Medicine Nepal, 2015)
Introduction: Health camp provides service to patients, near to their home, living in remote places with inadequate health facilities, like remote places of Nepal. This study was carried to assess the visual outcomes and complications associated with cataract surgery in camp patients, operated in a camp setting at community level in Sindhupalchowk.Methods: In a retrospective study, 23 outreach camp patients had undergone cataract surgeries with chamber intraocular lens implantation under peri-bulbaranaesthesia. Post-operative complications on day-1 were examined. Patients with any complications were managed conservatively and referred for further management to tertiary eye care centre.Results: 23 eyes underwent cataract extraction with intra ocular lens implantation. Small incision cataract surgery (SICS) was the commonest method (91.6%) used. 69.57% were female and 30.43% were male. The commonest first post- operative day complication was mild conjunctival congestion and sub-conjunctival haemorrhage. On Day-1 of post-operative Normal to Near-normal vision (6/6-6/18) was seen in 14(60.82), Moderate low vision 6/24 to 6/36 in 5 (21.74%), Severe low vision 6/60-3/60 in 3(13.04%), and Moderate blindness